The biology of Acia lineatifrons (Naude) (Homoptera : Cicadellidae) on grapevines in the Western Cape - Marais, Elleunorah (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1988)
The leafhopper, Acia lineatifrons (Naude) was identified as a pest on grapevines near Tulbagh in 1978 and has since been reported on grapevines all over the South Western Cape. A. lineatifrons causes browning of the leaves which often results in the shedding of the discoloured leaves. Heavy defoliation before harvest can result in sunburn damage to the grapes, whilst premature leaf loss after harvest adversely affects the ripening of the canes and the accumulation of reserves. This project was aimed at obtaining basic information on the biology and population dynamics of A. lineatifrons as well as to identify priorities for future research. This information is needed to develop a reliable crop-linked predictive model, methods for monitoring pest populations as well as to develop efficient short- and long-term control measures and pest management strategies. The life cycle of A. lineatifrons was studied in the laboratory. At 26°C the mean incubation period of the eggs was nine to eleven days, the mean developmental period for the five nymphal instars was 15 days and the minimum pre-oviposition period five to ten days. This adds up to a mean generation time of 29 to 36 days at 26°C. At 20°C the mean nymphal development period was 25 days, confirming the strong influence of temperature on the development rate. Fecundity was determined in the laboratory as the number of nymphs produced per female. The mean of 8,5 nymphs per female recorded at 26°C is very low compared to that of other leafhopper species (see Appendix 2). The low fecundity measured was most likely due to sub-optimal environmental conditions in the laboratory, a reduction in the suitability of the host plant under these conditions and handling of the females. The seasonal occurrence of A. lineatifrons on grapevines was studied over three seasons. It was found that the leafhoppers overwinter in the adult stage on indigenous Rubus spp, and that they enter the vineyard from the end of October until the beginning of November. Peak populations occurred between the middle of February and the end of March after which the population declined steadily towards the end of the season as the vine leaves were shed. The sex ratio of the overwintering population on R. chrysocarpus was heavily female biased, possibly due to differential mortality of the sexes. During the growing season the sex ratio was slightly male biased and reached equality on several occasions, both on the Rubus and on the grapevines. The movement of A. lineatifrons between the Rubus and the grapevines was investigated, but no evidence of a directional migration from the Rubus to the grapevines was found. Furthermore, no evidence was found to indicate that morphologically distinct short- and long-distance fliers, as found in Cicadulina species by Rose (1972b), exist in the A. lineatifrons population. Host preference tests also showed that adult leafhoppers apparently have no significant preference for grapevines to Rubus or vice versa. It seems, therefore, that the leafhoppers' move onto the grapevines at the beginning of the growing season is not prompted by a host preference. Chaboussou (1971) suggested that certain organic fungicides may cause leafhopper outbreaks because they affect the suitability of the vines as host plants and alter leafhopper fecundity. The effect of Mikal-M (active ingredient Fosetyl AL/Mancozeb), a systemic dithiocarbanate fungicide, on A. lineatifrons was investigated. Laboratory experiments showed no significant effect on fecundity and leaf analysis of potted vines treated with Mikal-M indicated no significant difference in total leaf nitrogen compared to untreated control plants. However, the field experiment on the effect of Mikal-M on the population build-up of the leafhopper showed that significantly more leafhoppers occurred on the vines treated with Mikal-M than on those treated with a conventional inorganic fungicide, copper oxychloride. In view of the far-reaching implications this can have on the viticultural industry, further research on the effects of organic fungicides on leafhopper populations is recommended to confirm the generality of these results so that recommendations regarding the use of these fungicides may be made. The question as to why A. lineatifrons became a pest only recently was raised. Three possibilities were considered, namely (1) that A. lineatifrons is a species of tropical origin which moved down the continent and became established in the Western Cape only recently, (2) that is has been in the Western Cape at least as long as the grapevines, but required prolonged exposure to establish itself on the new host and (3) that is has been on the vines for some time, but was noticed only recently when outbreaks occurred. These outbreaks could have been caused by the introduction of organic fungicides or the depletion of natural enemies by insecticides used to control other insects in the vineyards. Due to the lack of evidence this question could not be answered conclusively. Other research priorities that were established are the development of methods for damage assessment and monitoring of leafhopper populations, determining if A. lineatifrons can transmit grapevine virusses, the development of an economic threshold level and the identification of natural enemies of A. lineatifrons to enable the development of efficient pest management strategies (Summary, p. 63-65)
Keywords: Homoptera